Effect of Technological Mismatch on Photovoltaic Array: Analysis of Relative Power Loss - Stephen Nnamchi; Onyinyechi Nnamchi; Kevin Nwaigwe; Zaid Jagun; Johnson Ezenwankwo (Journal of Renewable Energy and Environment, 2021)
This study conducts a comparative evaluation of the performance of modules and the arrays under standard test conditions. An equivalent circuit model was developed alongside a computational scheme. The model input data were obtained from the manufacturer’s specification datasheets. They were used to analyse the maximum Fill Factor (FF) and Relative Power Losses (RPL) for Parallel (P), Series (S) and Series-Parallel (SP) configurations. For matching modules, the RPL was insignificant, but for mismatched modules, the parallel configuration (P) and series-parallel (SP) yielded RPL of 1.3 %, while the series configuration (S) produced RPL of 2.6 %. Thus, short circuit defects associated with the P and SP configuration were well below the open circuit defects associated with the series configuration (S). These results clearly show that the large photovoltaic plant needs to be configured with multiple blocks or strings of SP configuration in order to suppress RPL. In addition, the designer and installers of large solar power plants should adopt modules with uniform electrical and thermal properties in the construction of large solar power plants. The trivial RPL associated with the matched modules should be taken into consideration, as well.